IDNLearn.com is your go-to platform for finding reliable answers quickly. Join our knowledgeable community and get detailed, reliable answers to all your questions.

Obtain the following equations of motion for constant acceleration using the graphical method:

(i) [tex]\( v = u + at \)[/tex]

(ii) [tex]\( s = ut + \frac{1}{2} a t^2 \)[/tex]

(iii) [tex]\( v^2 = u^2 + 2as \)[/tex]

where:
- [tex]\( u \)[/tex] is the initial velocity
- [tex]\( v \)[/tex] is the final velocity
- [tex]\( t \)[/tex] is time
- [tex]\( a \)[/tex] is acceleration


Sagot :

Sure, let's derive the equations of motion for constant acceleration using the graphical method. We will use velocity-time graphs to help visualize and derive each equation.

### (i) [tex]\( v = u + at \)[/tex]

1. Imagine a velocity-time graph. The initial velocity [tex]\(u\)[/tex] is the velocity at time [tex]\(t=0\)[/tex]. This is represented by a point on the vertical axis (y-axis) of the velocity-time graph.
2. The velocity increases uniformly over time [tex]\(t\)[/tex] due to constant acceleration [tex]\(a\)[/tex]. Thus, the graph of velocity vs. time is a straight line with slope [tex]\(a\)[/tex].
3. The final velocity [tex]\(v\)[/tex] at time [tex]\(t\)[/tex] can be found from this straight line. The general equation of a straight line is given by:
[tex]\[ v = u + at \][/tex]

### (ii) [tex]\( s = ut + \frac{1}{2}at^2 \)[/tex]

1. Again, consider the velocity-time graph with initial velocity [tex]\(u\)[/tex].
2. The area under the velocity-time graph represents the displacement [tex]\(s\)[/tex].
3. For constant acceleration, the graph is a straight line with slope [tex]\(a\)[/tex]. Therefore, the area under the graph is a trapezoid.
4. The area of a trapezoid can be found by dividing it into two simpler shapes: a rectangle and a triangle.
- The rectangle's area, which extends from [tex]\(0\)[/tex] to [tex]\(t\)[/tex] (time) and up to [tex]\(u\)[/tex] (initial velocity), is [tex]\(u \times t\)[/tex].
- The triangle's area, which extends from [tex]\(u\)[/tex] to [tex]\(v\)[/tex] (final velocity) with the base as [tex]\(t\)[/tex] (time), is [tex]\(\frac{1}{2} \times t \times (v - u)\)[/tex].
5. Substituting [tex]\(v = u + at\)[/tex] from the first equation into the expression for the triangular area:
[tex]\[ \text{Area of triangle} = \frac{1}{2} \times t \times (u + at - u) = \frac{1}{2} \times t \times at = \frac{1}{2}at^2 \][/tex]
6. Therefore, the total displacement [tex]\(s\)[/tex] is:
[tex]\[ s = \text{Area of rectangle} + \text{Area of triangle} = ut + \frac{1}{2}at^2 \][/tex]

### (iii) [tex]\( v^2 = u^2 + 2as \)[/tex]

1. Using the first equation: [tex]\( v = u + at \)[/tex], solve for [tex]\(t\)[/tex]:
[tex]\[ t = \frac{v - u}{a} \][/tex]
2. Substitute this expression for [tex]\(t\)[/tex] into the second equation: [tex]\( s = ut + \frac{1}{2}at^2 \)[/tex]:
[tex]\[ s = u \left(\frac{v-u}{a}\right) + \frac{1}{2}a\left(\frac{v-u}{a}\right)^2 \][/tex]
3. Simplify the equation:
[tex]\[ s = \frac{u(v - u)}{a} + \frac{1}{2}a \cdot \frac{(v - u)^2}{a^2} \][/tex]
[tex]\[ s = \frac{uv - u^2}{a} + \frac{1}{2} \cdot \frac{(v - u)^2}{a} \][/tex]
[tex]\[ s = \frac{uv - u^2 + \frac{1}{2}(v^2 - 2uv + u^2)}{a} \][/tex]
[tex]\[ s = \frac{uv - u^2 + \frac{1}{2}v^2 - uv + \frac{1}{2}u^2}{a} \][/tex]
[tex]\[ s = \frac{\frac{1}{2}v^2 - \frac{1}{2}u^2}{a} \][/tex]
[tex]\[ 2as = v^2 - u^2 \][/tex]
4. Rearrange to get the final form:
[tex]\[ v^2 = u^2 + 2as \][/tex]

And there we have the three equations of motion derived using the graphical method: [tex]\(v = u + at\)[/tex], [tex]\(s = ut + \frac{1}{2}at^2\)[/tex], and [tex]\(v^2 = u^2 + 2as\)[/tex].